Pengaruh Budget Participation terhadap Managerial Performance melalui Budget Goal Difficulty dan Budget Goal Commitment sebagai Variabel Intervening - Stefani Stefani Stefani; Josua Tarigan (Business Accounting Review, 2016)
The enactment of MEA creates a business competition, especially in the ASEAN region will be tighter, thus requiring every company should have a good performance in order to have high competitiveness. Good performance related to managerial performance requires a good planning, and budgeting is one of the components in the plan. Budget participation is a budgeting approach that focuses on efforts to improve the performance of managers in order to achieve organization goals. The purpose of this research was to examine the influence of budget participation to managerial performance through budget goal difficulty and budget goal commitment as an intervening variable in companies around Surabaya. Data were collected from questionnaires (quantitative research). The sample of the study consistsed of managers of companies in Surabaya, with total 135 respondents. This study used Partial Least Square (PLS) analysis technique. The results of this study found that budget participation had positive influence to budget goal commitment, budget goal difficulty and managerial performance, which means the higher budget participation the higher manager’s commitment to achieved budget goal, budget goal difficulty, and managerial performance. Budget goal commitment also had positive influence to managerial performance, while budget goal difficulty had no influence.